The Effect of Leadership, Compensation and Motivation on Employee Performance in PT. Dua Mutiara - Yetiani, Yetiani; Krisnandi, Herry; Digdowiseiso, Kumba (International Journal of Social Service and Research, 2024)
This study aims to assess the impact of leadership, compensation, and motivation on employee performance at PT Dua Mutiara. Employing a quantitative descriptive approach, we conducted inferential analysis using primary data gathered through closed questionnaires distributed to 102 respondents. The study utilizes multiple linear regression analysis to test the research hypothesis. The findings reveal a positive and significant combined effect of leadership, compensation, and motivation on employee performance. In light of these results, PT Dua Mutiara is urged to conduct a detailed examination to identify specific areas for improvement. This analysis will serve as the foundation for addressing weaknesses and enhancing overall employee effectiveness. Emphasizing strong leadership, fair compensation, and motivational strategies will contribute to the ongoing efforts to boost employee performance within the organization.